Impact of randomised wmel Wolbachia deployments on notified dengue cases and insecticide fogging for dengue control in Yogyakarta City. Issue 1 (31st December 2023) - Indriani, Citra; Tanamas, Stephanie K.; Khasanah, Uswatun; Ansari, Muhammad Ridwan, Rubangi; Tantowijoyo, Warsito; Ahmad, Riris Andono; Dufault, Suzanne M.; Jewell, Nicholas P.; Utarini, Adi; Simmons, Cameron P.; Anders, Katherine L.
ABSTRACT: Background: Releases of Wolbachia ( w Mel)-infected Aedes aegypti mosquitoes significantly reduced the incidence of virologically confirmed dengue in a previous cluster randomised trial in Yogyakarta City, Indonesia. Following the trial, w Mel releases were extended to the untreated control areas, to achieve city-wide coverage of Wolbachia. Objective: In this predefined analysis, we evaluated the impact of the wMel deployments in Yogyakarta on dengue hemorrhagic fever (DHF) case notifications and on the frequency of perifocal insecticide spraying by public health teams. Methods: Monthly counts of DHF cases notified to the Yogyakarta District Health Office between January 2006 and May 2022 were modelled as a function of time-varying local wMel treatment status (fully- and partially-treated vs untreated, and by quintile of wMel prevalence). The frequency of insecticide fogging in wMel-treated and untreated areas was analysed using negative binomial regression. Results: Notified DHF incidence was 83% lower in fully treated vs untreated periods (IRR 0.17 [95% CI 0.14, 0.20]), and 78% lower in areas with 80–100% wMel prevalence compared to areas with 0–20% w Mel (IRR 0.23 [0.17, 0.30]). A similar intervention effect was observed at 60–80% wMel prevalence as at 80–100% prevalence (76% vs 78% efficacy, respectively). Pre-intervention, insecticide fogging occurred at similar frequencies in areas later randomised to wMel-treated and untreated arms of the trial. After w Mel deployment, fogging occurred significantly less frequently in treated areas (IRR 0.17 [0.10, 0.30]). Conclusions: Deployments of w Mel-infected Aedes aegypti mosquitoes resulted in an 83% reduction in the application of perifocal insecticide spraying, consistent with lower dengue case notifications in wMel-treated areas. These results show that the Wolbachia intervention effect demonstrated previously in a cluster randomised trial was also measurable from routine surveillance data.